Sex ratio and the evolution of aggression in fruit flies. Issue 1947 (17th March 2021) - Bath, Eleanor; Edmunds, Danielle; Norman, Jessica; Atkins, Charlotte; Harper, Lucy; Rostant, Wayne G.; Chapman, Tracey; Wigby, Stuart; Perry, Jennifer C.
Abstract : Aggressive behaviours are among the most striking displayed by animals, and aggression strongly impacts fitness in many species. Aggression varies plastically in response to the social environment, but we lack direct tests of how aggression evolves in response to intra-sexual competition. We investigated how aggression in both sexes evolves in response to the competitive environment, using populations of Drosophila melanogaster that we experimentally evolved under female-biased, equal, and male-biased sex ratios. We found that after evolution in a female-biased environment—with less male competition for mates—males fought less often on food patches, although the total frequency and duration of aggressive behaviour did not change. In females, evolution in a female-biased environment—where female competition for resources is higher—resulted in more frequent aggressive interactions among mated females, along with a greater increase in post-mating aggression. These changes in female aggression could not be attributed solely to evolution either in females or in male stimulation of female aggression, suggesting that coevolved interactions between the sexes determine female post-mating aggression. We found evidence consistent with a positive genetic correlation for aggression between males and females, suggesting a shared genetic basis. This study demonstrates the experimental evolution of a behaviour strongly linked to fitness, and the potential for the social environment to shape the evolution of contest behaviours.